Assessment of Nutritional Status And Functional Capacity of Rural Elderly Population In Chattogram, Bangladesh (Bangladesh Journal of Medicine, 2024)
Background: Bangladesh, like many developing countries, is experiencing population ageing. There is inadequate information regarding the prevalence of malnutrition and functional dependency in community-living rural senior residents in this country. The study aims to determine the nutritional status and functional capacity of the rural elderly population of Chattogram District of Bangladesh and to search for its associated factors. Methods: This community-based cross-sectional study included 213 subjects aged 60 years and over from two Upazilla of Chattogram district by a multistage random sampling technique. Sociodemographic and clinical data were collected using a structured questionnaire, nutritional status was assessed with the Mini Nutritional Assessment-Short Form (MNASF) tool and functional assessment was done using the Modified Barthel self-care index (BSI).Results: The participants’ mean age was 66.1 ± 6.5 years and 51.6 % was female. More than half of the participants (45.4%) were illiterate. The majority of them were living in a joint family with their spouse. About 70% of the participants were from lower socioeconomic classes, 82.2% were not engaged in any vocational activity, 74.6% were entirely dependent economically on others, and 110 (51.6%) had multi- morbidity. The prevalence of malnutrition and risk of malnutrition were 29.9% and 56.8% of the study sample, respectively. About 44% of the participants need help to perform their daily activities. Poor nutritional status was significantly more frequent in elderly subjects aged more than 70 years, in respondents living without a partner, and in older people with multi-morbidity. Conclusion: Poor nutritional status was commonly observed among older adults living in rural areas in Chattogram. The associated factors should be further considered for targeting particularly vulnerable individuals.Bangladesh J Medicine 2024; 35: 76-81